Statistical Sources for the Study of Disaster Risk Management in Central America. The DesInventar Database and its Contributions for Historical Research - Zúñiga Arias, Yolanda (2019)
The main objective of this article is to describe the potential of the DesInventar database as a historical source. In particular, the contributions of “statistical repository” for research on disaster risk management with a Central American perspective are mentioned.